Iran Diabetes Research Roadmap (IDRR) Study; Nutrition in Diabetes: A Review Article - Zarin Sadat EBRAHIMI; Maryam PEIMANI; Leila AZADBAKHT; Ensieh NASLI-ESFAHANI; Farideh RAZI; Bagher LARIJANI (Tehran University of Medical Sciences, 2017)
Background: The study aim was to reports detailed characteristics of nutrition research in field of diabetes, and recognize knowledge gap in nutrition science in diabetes in Iran. Methods: Online databases of PubMed, Web of Science and Scopus as well as national databases including SID, IranMedex, and Magiran were searched up to 2015 to identify eligible articles. Finally, 378 articles were included. Results: Final articles were categorized based on WHO and Australian classifications, study design and subject area. The most number of studies (80%) was related in strategies and interventions of health-related outcome group the WHO classification. The most percentage of publications in Australian classification system was allocated to clinical researches (78%) and the least studies were health service studies (0.08%). The most common designs used in the obtained documents (41%) were Randomized Clinical Trials (RCT) and about 17% of publications were animal studies. Cohort studies were the least studies among the obtained documents. The most common subject was type 2 Diabetes Mellitus and its complications followed by DM management (64%, n=241). The least numbers of publications were dedicated to GDM (Gestational Diabetes Mellitus). There was a large ascent in studies during 2010-2011 and 2012-2013. Conclusion: Available evidence provides very good support for the role of nutrition diets in the prevention and management of all types of diabetes. This systematic review indicates trend of nutrition researches in diabetes was noticeable flourished, while the important subjects in diabetes studies are forgotten or unimportance.